Untitled - (:unkn) unknown (My University, 2008)
Photograph of a group of East Indian children standing next to a stand pipe.
Colour:Black and White ; Style:Portrait ; Other:Bordered, Undivided
Keywords: Postcards; Rural children; Rural conditions